Coumarin as a Prominent Lead Nucleus, by Virtue of its Diversity in Bioactivity and Therapeutic Potential in Present Scenario of Chemical and Pharmaceutical Research - Barve, Ashutosh (Journal of Medical Biomedical and Applied Sciences, 2016)
Coumarins are well-known natural products displaying a broad range of biological activities1. Many naturally occurring as well as synthetic derivatives of coumarin have been found to possess diverse biological activities namely anticoagulant2, spasmolytic3, anthelmintic4, diuretic5 and anti-inflammatory6 activities. 4-Pyridyl and 4-piperidyl coumarin have been found to exhibit CNS depressant and analgesic activities in animal models7-9. The halogenated furanyl coumarins show antimicrobial action10, whereas isoxazolinyl and oxadiazolyl coumarins 11 inhibit enzymes like glucouronidase and 1, 2-lipoxygenase. Further, 2-biheterocyclic benzofurans with furan12, chromone13 ring systems exhibit antibacterial, psychotropic and anti-inflammatory properties.